Website and Social Media Usage for Internet Reporting (Case Study at Zakah Managament Organization) - Nurkhin, Ahmad; ., Kardoyo; ., Muhsin; Mukhibad, Hasan; ., Sumiadji (KnE Social Sciences, 2020)
Zakah Management Organization (ZMO) is demanded to improve its transparency and accountability including presenting financial and non-financial information by internet. This study aims to describe and compare the usage of website and social media to report many kinds of information by ZMO at state university in Indonesia. This is descriptive qualitative study. The research object is website and social media of Rumah Amal Salman, Rumah Amal Lazis UNNES and LAZIS UNS. Moreover, the data is collected by observation and documentation method. In addition, the data then analyzed by content analysis. Results show that those ZMO have utilized well both website and social media for internet reporting, especially non-financial information. Website is used to deliver organization profile, product information and other important information that can be useful for donor or muzakki. However, there are two ZMO that have not used website and social media to report their financial state. It is Rumah Amal Lazis UNNES which conducts internet financial reporting but limited to Fund Statement. Furthermore, Facebook and Instagram are considered as social media that mostly used by ZMO. Twitter has not been actively used. In addition, YouTube application has not been maximized. In summary, interaction to muzakki through social media needs to be improved by the ZMO. Keywords: internet reporting, website, social media, facebook, instagram, twitter, ZMO